Global finance at risk : on real stagnation and instability - Sen, Sunanda (New Delhi, 2004)
The book changes the conventional wisdom of market efficiency in the context of t od ay's 'high finance', and points towards its limitations in generating real growth and development for developing countries. The book charts out an alternate route of global finance capable of generating real demand and activity. It will interest economists and professionals in the financial sector. About The Author: Sunanda Sen Professor of Economics, Jawaharlal Nehru University, Delhi.
Keywords: International capital flow